The Effects of Verbal Guidance on the Intensity of First Stage of Labor Pain in the Primigravida Mother In Community Health Center of Kassi-Kassi Makassar - Nurhidayat Triananinsi; Linda Andriani; Mudyawati Kamaruddin (USN Scientific Journal, 2020)
One of the main factors influencing labor is the inadequate psychological condition that makes a person feel anxious. One effort to solve anxiety problem is with verbal guidance that with gently and soothingly words can reduce the pain experienced of the mother. This study aims to determine the effect of verbal guidance on the intensity of first phase labor pain in primigravida in-mother mothers. This type of research used quasi- experimental design with one group Pre test-post design techniques. The population in this study were all mothers who gave birth normally in Community Health Center (CHC) of Kassi-Kassi Makassar during March up to June 2019. The sample in this study was 30 respondents using purposive sampling technique, the data used are primary data. Data analysis was performed with the Wilcoxon Test. Based on the Wilcoxon Test results obtained p value = 0,000 which is smaller than the significance degree (α = 0.05). Based on the results of the analysis Ha (Alternative Hypothesis) was accepted and H0 (Zero Hypothesis) was rejected, it means there is the influence of verbal guidance on the intensity of labor pain on the first phase of primigravida mothers in CHC of Kassi-kassi Makassar. We hope to be able to assist midwifery services in improving maternal health services by applying good verbal guidance methods as one of interventions in reducing maternal pain.